2001
DOI: 10.4269/ajtmh.2001.64.283
|View full text |Cite
|
Sign up to set email alerts
|

Specific heterologous F(ab')2 antibodies revert blood incoagulability resulting from envenoming by Lonomia obliqua caterpillars.

Abstract: Abstract. Contact with Lonomia obliqua caterpillars results in a bleeding syndrome characterized by hemorrhage and blood coagulation disturbances. Conventional therapy using antifibrinolytics or cryoprecipitates has been unable to treat pathophysiologic alterations. As antivenoms are effective therapy for treatment of victims of venomous animals, a process of manufacturing a specific antilonomic serum by immunizing horses with Lonomia caterpillar bristle extracts (LBE) was developed. Lonomia caterpillar bristl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 18 publications
2
24
0
3
Order By: Relevance
“…97 It should be noted that antifibrinolytics do not work for stings caused by L obliqua and may exacerbate the clinical symptoms. 132,135 Whole blood and fresh-frozen plasma may worsen hemorrhagic symptoms in stings from both species and should be avoided. 97,135 CONCLUSIONS Moths and their caterpillars may cause dermatologic or systemic symptoms in humans.…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…97 It should be noted that antifibrinolytics do not work for stings caused by L obliqua and may exacerbate the clinical symptoms. 132,135 Whole blood and fresh-frozen plasma may worsen hemorrhagic symptoms in stings from both species and should be avoided. 97,135 CONCLUSIONS Moths and their caterpillars may cause dermatologic or systemic symptoms in humans.…”
Section: Pathologymentioning
confidence: 99%
“…An effective antivenin against Lopap has been produced to counteract the hemorrhagic diathesis from L obliqua envenomation. 131,132 It has been successful in preventing severe hemorrhage in two large series of patients, 133,134 and is considered the cornerstone of current therapy. 97 Stings caused by L achelous should be treated with cryoprecipitate, purified fibrinogen, or antifibrinolytic drugs, such as aprotinin and e-aminocaproic acid.…”
Section: Pathologymentioning
confidence: 99%
“…Based on that, some studies were carried out using caterpillars in the 5th instar [38] . Moreover, the anti-lonomic serum is produced in horses at Instituto Butantan using bristle extract from L. obliqua caterpillars in the 5th instar [36] . At this stage, many molecules from the larva play important roles in developmental process, proliferation and wound repair in the late larval period [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the Butantan Institute has started to produce and distribute an antilonomic serum (SALon). This serum has proved highly effective in reversing the hemorrhagic syndrome caused by the venom of L. obliqua [33,35,36] . In 2004, Caovilla and Barros demonstrated that low doses of the antilonomic serum were capable of reversing changes in blood coagulation in less than 48 h for the majority of patients with moderate or severe envenoming [37] .…”
Section: Clinical Profilementioning
confidence: 99%
“…It appears that our attempt to generate a catalog containing the putative toxic proteins of the caterpillar is an effective approach to generate testable hypotheses on the molecular basis of envenomation. It may help to find candidate proteins for development of a reliable diagnostic kit for this envenomation and for the improvement of serum production (Rocha- Campos et al, 2001;Theakston et al, 2003). SDS-PAGE analysis of L. obliqua bristle and tegument extracts, hemolymph, and cryosecretion.…”
Section: Obliqua Venomous Components: Insights For Their Role In Tmentioning
confidence: 99%